Role of HNF4alpha-cMyc interaction in liver regeneration after partial hepatectomy - Kotulkar, Manasi; Paine-Cabrera, Diego; Venneman, Kaitlyn; Apte, Udayan (Frontiers in Endocrinology, 2024)
Background Hepatocyte nuclear factor 4 alpha (HNF4α) is the master regulator of hepatic differentiation. Recent studies have also revealed the role of HNF4α in hepatocyte proliferation via negatively regulating the expression of proto-mitogenic genes, including cMyc. Here, we aimed to study the interaction between HNF4α-cMyc during liver regeneration after partial hepatectomy (PHX). Methods Wild-type (WT), hepatocyte-specific knockout of HNF4α (HNF4α-KO), cMyc (cMyc-KO), and HNF4α-cMyc double knockout (DKO) mice were subjected to PHX to induce liver regeneration. Blood and liver tissue samples were collected at 0h, 24h, 48h, 7D, and 14D after PHX for further analysis. Results WT, HNF4α-KO, cMyc-KO and DKO mice regained liver weight by 14 days after PHX. The deletion of cMyc did not affect liver regeneration, which was similar to the WT mice. WT and cMyc-KO mice started regaining liver weight as early as 24 hours after PHX, with a peak proliferation response at 48 hours after PHX. HNF4α- KO and DKO showed a delayed response with liver weight increase by day 7 after PHX. The overall hepatocyte proliferation response by DKO mice following PHX was lower than that of other genotypes. Interestingly, the surviving HNF4α-KO and DKO mice showed re-expression of HNF4α at mRNA and protein levels on day 14 after PHX. This was accompanied by a significant increase in the expression of Krt19 and Epcam, hepatic progenitor cell markers, in the DKO mice on day 14 after PHX. Conclusion These data indicate that, in the absence of HNF4α, cMyc contributes to hepatocyte-driven proliferation to compensate for the lost tissue mass. Furthermore, in the absence of both HNF4α and cMyc, HPC-driven proliferation occurs to support liver regeneration.